2021
DOI: 10.1103/physrevmaterials.5.123802
|View full text |Cite
|
Sign up to set email alerts
|

General model for the kinetics of solute diffusion at solid-solid interfaces

Abstract: Solute diffusion through solid-solid interfaces is paramount to many physical processes. From a modeling point of view, the discontinuities in the energy landscape at a sharp interface represent difficulties in predicting solute diffusion that, to date, have not been solved in a consistent manner across length scales. Using an explicit finite volume method, this work is the first to derive numerical solutions to the diffusion equations at a continuum level while including discrete variations in the energy land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The adsorption sites on the surface of the Fe 3 O 4 @CTS/SBC composite adsorbent were mainly occupied by Cu 2+ , which began to enter the micropores of the composite adsorbent and was adsorbed by the micropores. At the third stage of adsorption, the adsorption sites on the surface and inside the pores of the Fe 3 O 4 @CTS/SBC composite adsorbent were basically saturated, and the adsorption reached an equilibrium state 38 . Based on the particle diffusion model, it could be concluded that the adsorption of Cu 2+ by the Fe 3 O 4 @CTS/SBC composite adsorbent was not only a chemical chelation, but also an intraparticle diffusion process.…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption sites on the surface of the Fe 3 O 4 @CTS/SBC composite adsorbent were mainly occupied by Cu 2+ , which began to enter the micropores of the composite adsorbent and was adsorbed by the micropores. At the third stage of adsorption, the adsorption sites on the surface and inside the pores of the Fe 3 O 4 @CTS/SBC composite adsorbent were basically saturated, and the adsorption reached an equilibrium state 38 . Based on the particle diffusion model, it could be concluded that the adsorption of Cu 2+ by the Fe 3 O 4 @CTS/SBC composite adsorbent was not only a chemical chelation, but also an intraparticle diffusion process.…”
Section: Discussionmentioning
confidence: 99%